Flexible facility requirements for strategic planning of airport passenger terminal infrastructure - Waltert, Manuel; Jimenez Perez, Edgar; Pagliari, Romano (Taylor & Francis, 2025)
Facility requirements determine how and when the capacity of airport passenger terminal facilities is adjusted over time to meet expected demand. Given high levels of uncertainty inherent in long-term airport planning, under and over provision of capacity is a recurrent risk, as conventional strategic planning methods fail to adapt dynamically to changing circumstances. This paper introduces a novel flexible capacity expansion model for airport terminals that considers simultaneously real options ‘on’ and ‘in’ systems. The model is validated for the provision of check-in facilities at Zurich Airport. Results confirm suggestions in the literature that incorporating flexibility creates planning and financial advantages over conventional alternatives. Indeed, for the case of Zurich, the financial value of the flexible alternative is approximately 5% higher than the best conventional phased plan. This also suggests that phasing developments can be carefully devised to produce satisfactory outcomes that enable ex-post application of flexibility ‘on’ systems.
Keywords: Flexible airport strategic planning; airport passenger terminal facility; facility requirements; real options; decision rules